Wypisy źródłowe do biografi i polskich biskupów i opatów z czasów Rzeczypospolitej Obojga Narodów oraz niewoli narodowej doby zaborów (XVI-XIX w.). Część XI - Prokop, Krzysztof R. (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The eleventh part of the cycle of the Source extracts for the biography of the Polish bishops and abbots from the time of the Polish-Lithuanian Commonwealth and the Partitions of Poland was divided into two separate subject areas, the fi rst of which is the continuation of the material presented in the previous part and it contains the information about the ordination of bishops (date, place, main consecrator, co-consecrators). This subject area includes notes regarding anointment of a total of 100 hierarchs of the 16th-19th centuries, representing mainly the Latin rite (only four Eastern rites). The other subject area, with the heading monastica, presents the materials for the biographies of abbots (this number also includes commendatory abbots) and abbesses of the Polish-Lithuanian-Ruthenian lands, representing both Latin and Greek-Catholic rite (Basilian Archimandrites). The total number is 43 people from the 17th, 18th and 19th centuries. The information presented in this and the previous ten parts of the Source extracts gives way to the study which could contribute significantly to the development in the area of biographical lexicons of Old Polish bishops and abbots. The issuing of such publication is something that is urgently demanded from the native church historiography as in this respect it remains far behind historiographies of other countries with Christian traditions.